Gambaran Tingkat Pengetahuan Ibu Hamil Tentang Pencegahan Penularan Sifilis pada Bayi Baru Lahir di Puskesmas Perak Timur Kota Surabaya - Galuh Zediara; Dewi Setyowati; Gadis Meinar Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Background: Syphilis during pregnancy can cause miscarriage, premature birth, low birth weight, stillbirth, or congenital syphilis. In Indonesia, syphilis has reportedly increased by 70% in the last 5 years. And unfortunately, syphilis cases are still high in big cities in Indonesia, especially Surabaya. The aim is to understand the level of knowledge of pregnant women regarding efforts to prevent the transmission of syphilis to newborns at the Perak Timur Community Health Center, Surabaya City. Method: The choice was descriptive observational with a cross-sectional approach. The total number of respondents involved was 30 people. The inclusion criteria were pregnant women in the 1st, 2nd, and 3rd trimesters who visited and received antenatal care at the Perak Timur Community Health Center, Surabaya City. Meanwhile, the exclusion criteria for this study were pregnant women with special needs. This research was conducted at the Perak Timur Community Health Center, Surabaya City, during September 2023. Samples were collected using a purposive sampling technique. Results: The majority of respondents, namely 56.6%, had a good level of knowledge about preventing the transmission of syphilis to newborns; 30% had a minimal level of knowledge regarding preventing the transmission of syphilis to newborns; and the other 13.3% had some knowledge. which is quite related to anticipating the transmission of syphilis to newborns. Conclusion: The majority of respondents have a good level of knowledge regarding preventing the transmission of syphilis to newborns.